Protecting oracle database 12c - Wright, Paul (Apress, 2014)
Protecting Oracle Database 12c helps you solve the problem of maximizing the safety, resilience, and security of an Oracle database whilst preserving performance, availability, and integration despite ongoing and new security issues in the software. The book demonstrates, through coded examples, how you can enable the consolidation features of Oracle Database 12c without increasing risk of either internal corruption or external vulnerability. In addition, new protections not publicly available are included, so that you can see how demonstrable risk improvements can be achieved, measured, and reported through Enterprise Manager 12c. Most importantly, the challenge of privileged access control within a consolidation environment will be addressed, thus enabling a safe move to greater efficiency.